Ningbo FOTILE Kitchen Ware Co., Ltd. - McFarlan, F. Warren (Franklin Warren); Zheng, Xiaoming; Fang, Yuren ([London] : SAGE, 2016)
On 25 March 2013, Ningbo FOTILE Kitchen Ware Co., Ltd. (hereinafter referred to as 'FOTILE') launched its new generation exhaust hood series. The company's staff members were proud of this latest product that combines cutting-edge design with super effective, low-noise fume removal technology. The media had also praised this product as China's most effective range hood. FOTILE President Mao Zhongqun, however, was not concerned about the release of the company's new products, but rather about the sustainability of the company's technological innovation capability, as well as its culture and how they would impact sales. This case study discusses these concerns.
Originally Published in: McFarlan, F. W., Zheng, X., & Fang, Y. (2013). Ningbo FOTILE Kitchen Ware Co., Ltd. 6-813-351. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Ningbo fang tai chu ju you xian gong si; Technological innovations -- China -- Case studies; Corporate culture -- China -- Case studies